Effect of Benzalkonium Chloride as Antibacterial Activity on Dental Composites Containing Nano-Titanium dioxide Particles: in vitro study. - Atbayga A1, Abdelaaziz M2* (AlQalam Journal of Medical and Applied Sciences, 2020)
Aim: The objective of this in vitro study was to evaluate the antimicrobial activity of resin-based dental composites containing Nano-Titanium dioxide Particles that were set with benzalkonium chloride (BzCl). Methods: TiO2 nanoparticles were treated with (3-mercaptopropyl) trimethoxysilane (MPTMS). Three groups of resin-based dental composites were prepared, namely: Group 1 (an untreated TiO2 nano-composite), Group 2 (treated TiO2 nano-composite) and Group 3 (treated TiO2 nano-composite was combined with three concentrations of benzalkonium chloride (BzCl). Five bacteria were selected and tested against the composite nano-TiO2 particles, namely, Escherichia coli (E. coli), Staphylococcus aureus (S. aureus), Enterococcus faecalis (E. faecalis), and Pseudomonas aeruginosa (P. aeruginosa), were grown on Müller-Hinton Agar (MHA), and Streptococcus mutans (S. mutans) was grown on Brain Heart Infusion (BHI) agar. Results: The results of the present study showed that neither of the groups of TiO2 nano-composites, (untreated TiO2 nano-composite and treated TiO2 nano-composite) exhibited antimicrobial activity against the pathogens. Only preparations of TiO2 nano-composites at a concentration of 3 %m/m of BzCl showed antimicrobial activity against S. aureus. Antimicrobial activity against S. mutans, E. coli, P. aeruginosa, E. faecalis and S. aureus, were only realized at a concentration of 10 %m/m for BzCl. Conclusions: Dental composites nano-TiO2 particles prepared and provided with antibacterial substances such as BzCl may prevent the growth of bacteria and may be beneficial as an additive in dental restorations.